The Potential of RICOSRE in Improving Scientific Reasoning of Students with Different Academic Ability - Riri Rahmadani Putri; Susriyati Mahanal; Fatchur Rohman (Pascasarjana Universitas Negeri Malang (UM), 2020)
Abstract: The research aims to analyze the potential of the RICOSRE learning model in improving students' scientific reasoning abilities on different academic abilities. This research is a quasi-experimental research. SMAN 1 Malang and SMAN 7 Malang became a place of research with a sample of 188 students. The research design is Noneqivalent pretest - posttest control desaign group. Research data in the form of the acquisition of essay test scores. Essay test results were analyzed using anacova. Based on the research result it is proved that there is a potential of the RICOSRE on students' scientific reasoning abilities on different academic abilities.Abstrak: Penelitian bertujuan untuk menganalisis potensi model pembelajaran RICOSRE dalam meningkatkan kemampuan penalaran ilmiah siswa dengan kemampuan akademik berbeda. Penelitian ini merupakan penelitian quasi-eksperimien. SMAN 1 Malang dan SMAN 7 Malang menjadi tempat penelitian dengan jumlah 188 siswa sebagai sampel. Data penelitian berupa perolehan skor tes esai. Hasil tes esai dianalisis menggunakan anakova. Berdasarkan hasil penelitian diketahui adanya potensi model pembelajaran RICOSRE terhadap kemampuan penalaran ilmiah siswa pada kemampuan akademik berbeda.